GERAKAN LITERASI SEKOLAH TUMBUHKAN KETERAMPILAN ABAD KE-21 - Erna Sari Agusta; Susiah Budiarti (Jurnal Lingkar Mutu Pendidikan, 2024)
Literacy activities carried out at MTsN 28 Jakarta do not accommodate students' abilities in drawing conclusions from reading, writing and speaking. As technology advances, the goals of literacy activities have developed in line with educational goals that lead to 21st century skills, mastery of digital literacy and character. The aim of this research is to determine the forms of development of literacy activities at MTs Negeri 28 Jakarta and their impact on 21st Century skills. This type of research is qualitative research with research subjects totaling 540 people. Data collection techniques were carried out using observation and interviews. Qualitative data was analyzed descriptively using a data analysis technique framework consisting of data reduction, data presentation, and drawing conclusions. The development of literacy activities is said to have an impact if there is an increase in the number or reaches a minimum of 75% of students who are involved and contribute. The results of the research conclude that the form of implementing literacy activities at MTs Negeri 28 Jakarta is carried out by getting into the habit of reading 15 minutes before lessons start, making class media, holding a literacy festival, holding morning literacy performances, preparing short story and poetry anthologies, preparing research proposals, and using the web as a digital literacy medium. The literacy activities carried out can foster 21st Century skills, mastery of digital literacy and character.